Cryopreservation as Optimizing Factor in Therapeutic Effect of Products of Embryofetoplacental Complex (PEFPC) Part 1. Pathology of autoimmune genesis as assessment model of therapeutic effect of PEFPC application - Goltsev, A. N.; Popova, K. N.; Sirous, M. A. (Problems of Cryobiology and Cryomedicine, 2006)
The possibility of using model autoimmune diseases for estimating a therapeutic efficiency of cryopreserved products of embryofetoplacental complex (PEFPC) is substantiated. With the example of autoimmune hemolytical anemia there has been shown a multi-profile change of the state of lymphohemopoietic complex of the animals with this pathology. The changes in various links of immune system during pathology development are emphasized. There is noted a possible dependence of their manifestation extent on disorder of harmonic interaction in neuroimmune endocrine block of an organism that stipulates the necessity of treatment of such diseases by preparations with a polyfunctional orientation effect, namely PEFPC.